The Effect of Orthodontic Treatment on Improving the Rapid Healing of Gingival Tissue: A Microscopic Study - Ahmed Abuhajar (AlQalam Journal of Medical and Applied Sciences, 2025)
People widely acknowledge orthodontic treatment as a method to align teeth and improve dental function, but there is limited knowledge about its impact on gingival tissue healing. An examination of orthodontic gingival tissue repair at the microscopic level examines both histological and immunohistochemical markers in this study. The research evaluated the behavior of cellular proliferation and vascular development within orthodontic patient gingival tissue through the use of Ki-67 to measure cellular proliferation and CD31 for vascular development analysis. The researchers collected gingival tissue samples from patients undergoing fixed orthodontic treatment at three specific time points, which included before treatment and during active orthodontic movement and finally following finishing treatment. Tissue structure analysis took place through histological techniques alongside immunohistochemical analysis of cell activity and vascular development changes. The research utilized paired t-tests and ANOVA statistical tests to verify healing rate distinctions. Tissue examination demonstrated that gingival cells increased their proliferation by 45% (based on Ki-67 expression) and developed more blood vessels by 38% (based on CD31 expression) after treatment when compared to pre-treatment measurements. After orthodontic treatment, the tissue exhibited improved collagen synthesis, together with rearranged tissue structures and reduced inflammation parameters based on histological assessment. The therapeutic powers of orthodontic forces expedite gingival tissue healing by stimulating cellular activity and developing better blood vessels in the healing region. Research results emphasize the need to understand orthodontic biological effects on periodontal health because they deliver essential data about treatment protocol optimization. The research advances orthodontic science by proposing specific treatment measures that enhance gingival healing throughout the therapeutic process and following treatment completion.